Depletion of circ_0007841 inhibits multiple myeloma development and BTZ resistance via miR-129-5p/JAG1 axis - Wang, Yan; Lin, Quande; Song, Chunge; Ma, Ruojin; Li, Xiaojie (Cell cycle (Georgetown, Tex.), 2020)
Circular RNAs (circRNAs) possess important regulatory effects on multiple myeloma (MM) progression. Here, we aimed at exploring the function of circ_0007841 in MM and the underlying molecular mechanism. Expression of circ_0007841, microRNA (miR)-129-5p and Jagged1 (JAG1) was determined via qRT-PCR or western blot assay. Methyl thiazolyl tetrazolium (MTT) assay was applied to examine cell viability and IC50 value of MM cells to bortezomib (BTZ). Colony formation assay was performed to analyze cell proliferation. Moreover, cell apoptosis was assessed by flow cytometry and western blot analysis. Cell metastasis was evaluated by wound healing assay and Transwell assay. Function of circ_0007841 in vivo was determined by xenograft tumor assay. Target relationship between miR-129-5p and circ_0007841 or JAG1 was confirmed via dual-luciferase reporter, RNA immunoprecipitation (RIP) and pull-down assays. The up-regulation of circ_0007841 and JAG1, and the down-regulation of miR-129-5p were detected in MM bone marrow aspirates and cells. Circ_0007841 knockdown significantly repressed cell proliferation, chemoresistance, and metastasis, while contributed to apoptosis of MM cells in vitro, and reduced tumor growth in vivo. Circ_0007841 targeted miR-129-5p, and miR-129-5p inhibition reversed impact of silencing of circ_0007841 on MM cells. JAG1 was a mRNA target of miR-129-5p, whose overexpression could undermine the miR-129-5p-mediated effects on MM cells. Circ_0007841 positively regulated JAG1 expression via absorbing miR-129-5p. Circ_0007841 knockdown inhibited MM cell proliferation, metastasis and chemoresistance through modulating miR-129-5p/JAG1 axis, suggesting that circ_0007841 might serve as a potential therapeutic target of MM.